TANGGUNG JAWAB DISTRIBUTOR DALAM CACAT PRODUK PADA TRANSAKSI E-COMMERCE MELALUI FACEBOOK - Nindri Sari, Nessya; Westra, I Ketut; Rudy, Dewa Gde (Kertha Wicara : Journal Ilmu Hukum, 2013)
Social dynamics in today's world has changed rapidly. Electronic commerce is aproduct of the growth in the field of information and communication technology (ICT)has revolutionized the way in which commercial transactions being conductedworldwide. Distributors have realized the potential to utilize social media in terms ofcreating brand awareness, generate revenue, get feedback from consumers. But thereare also distributors who cheat and run away from the responsibility of making theconsumer loses. Consumer protection should receive more attention, because it hasbecome part of the economic development of Indonesia.
Keywords: Electronic commerce, responsibility, distributors.